Ceramic composite material spring and preparation method thereof

By depositing a silicon carbide ceramic layer on the surface of the spring mold and combining a silicon carbide fiber braid and a boron nitride interface phase layer, ceramic composite springs were prepared, which solved the strength reduction and rebound of existing high-temperature resistant springs in high-temperature environments. The problem of loss of capability achieves higher axial stiffness and rebound retention, as well as better high temperature and irradiation stability.

CN119390453AActive Publication Date: 2025-02-07NORTHWESTERN POLYTECHNICAL UNIV
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202411551726.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-07
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

The existing high-temperature resistant springs have reduced strength and lost rebound capability in high-temperature environments, limiting their application in nuclear reactors.

Method used

A ceramic composite material is used to prepare a spring, and a silicon carbide ceramic layer is deposited on the surface of the spring mold by chemical vapor deposition method, combining the silicon carbide fiber braid and the boron nitride interface phase layer to form a multi-layer structural spring.

Benefits of technology

It improves the axial stiffness and rebound retention of the spring, enhances its stability in high temperature, neutron radiation and oxidative environments, and extends the service life of the spring.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390453A_ABST
    Figure CN119390453A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of high-temperature-resistant springs, and discloses a ceramic composite material spring and a preparation method thereof. The preparation method comprises the following steps: depositing silicon carbide on the surface of a spring mold by adopting a chemical vapor deposition method to obtain a stabilized spring mold; a plurality of strands of silicon carbide fibers are stranded and woven into a fiber woven body, the fiber woven body is embedded into a stabilizing spring mold to be fixed, and a spring woven body is obtained; a chemical vapor deposition method is adopted, an interface phase layer and a ceramic matrix layer are sequentially deposited inside and on the surface of the spring woven body, and then the spring woven body is further coated with a rare earth co-permeation layer through an embedding permeation method; and polishing after preparing a surface reinforcing layer to obtain the ceramic composite material spring. The preparation technology is low in operation difficulty, organic combination of all material components in the spring is achieved, the bonding strength between fibers and all layers is improved, and the ceramic composite material spring has good stability in the neutron irradiation environment and can tolerate the inert or aerobic environment at the temperature of 1350 DEG C for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high temperature resistant springs, and in particular to a ceramic composite material spring and a preparation method thereof. Background Art

[0002] Nuclear reactor control technology is one of the key technologies to ensure the safe and stable operation of nuclear reactors, and is a research focus and hotspot in various countries. The control rod is the core component for controlling the start and stop of the reactor. When the control rod moves along the axial direction of the core, a spring array is required to buffer the movement of the control rod to avoid hard collisions between structural elements, which in turn causes damage to the core. Taking a typical helium-xenon reactor as an example, when the reactor is operating, the core structure is in a high temperature environment of 700°C to 1300°C, which puts higher demands and challenges on the spring's neutron irradiation resistance, high temperature resistance, long-term performance stability and rebound characteristics.

[0003] The heat-resistant stainless steel X35CrMo17 and X30WCrV53 in the prior art can withstand high temperatures of 400°C, the high-temperature alloy InconelX750 and the high-temperature alloy InconelX718 can withstand high temperatures of 600°C, and the high-temperature alloy Nimonic90 can withstand temperatures of up to 700°C. However, when the operating temperature exceeds 900°C, the strength of the above-mentioned high-temperature alloys will be significantly reduced, thereby reducing the performance of the springs prepared by the above-mentioned high-temperature alloys or even losing their resilience, thereby limiting the application of the above-mentioned high-temperature alloys in nuclear reactors.

[0004] In order to solve the above technical problems, the technical personnel in the field have proposed to improve the performance of spring materials by introducing carbon fiber reinforcements, and the prior art introduces carbon fiber reinforcements by using a precursor conversion process and a carbon fiber weaving method. Among them, the precursor conversion process first uses a melt molding process to prepare a spring preform, densifies it by a precursor conversion process, and deposits a SiC anti-oxidation coating by a CVD process to prepare a unidirectional carbon fiber reinforced silicon carbide. Although this preparation method can achieve the performance of a carbon fiber reinforced silicon carbide ceramic matrix composite spring to a certain extent, the preparation method is complex and difficult to operate, and the prepared spring is prone to degradation and damage in the neutron irradiation environment of a nuclear reactor or other aerobic environments, resulting in the service life of the spring not meeting the requirements of engineering use. The above carbon fiber weaving method refers to weaving multiple strands of carbon fiber into a carbon fiber rope, and then depositing silicon carbide material on the surface of the formed carbon fiber rope by a vapor deposition method to achieve the composite of carbon fiber and silicon carbide, but the spring formed by this method is prone to fiber scattering and matrix shedding under large deformation conditions, and also has the problem of insufficient neutron irradiation resistance and antioxidant performance. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a ceramic composite material spring and a preparation method thereof.

[0006] A ceramic composite material spring and a preparation method thereof of the present invention are realized by the following technical solutions:

[0007] The present invention provides a method for preparing a ceramic composite material spring, comprising the following steps:

[0008] Step 1, select the mold:

[0009] Select the corresponding spring mold according to the required spring structure.

[0010] It should be noted that in order to ensure that the spring mold used in the present invention can achieve the actual required spring structure, the present invention preferably obtains a mold model with a corresponding structure through three-dimensional software design based on the geometric parameters of the required spring, and then obtains the corresponding spring mold through mechanical processing.

[0011] In some preferred embodiments of the present invention, the present invention uses graphite as raw material and obtains a graphite spring mold through mechanical processing. The graphite material can maintain good physical and chemical stability in the subsequent high-temperature treatment process, and has good physical and chemical compatibility with the preparation material of the spring body used in the present invention, which can ensure the precise material composition and geometric dimensions of the spring material.

[0012] Step 2, stabilization of the spring mold:

[0013] In an atmosphere containing a silicon carbide source, a silicon carbide ceramic layer is deposited on the surface of the spring mold by using a chemical vapor deposition method to obtain a stabilized spring mold.

[0014] It should be noted that, before the spring preparation raw materials are embedded, the present invention first uses chemical vapor deposition technology to stabilize the spring mold, so as to remove impurities in the spring mold through the stabilization treatment and improve the quality of the subsequently formed spring finished product.

[0015] Moreover, the present invention performs chemical vapor deposition in an atmosphere containing a silicon carbide source, so that the silicon carbide source can produce silicon carbide during the chemical vapor deposition process, and the produced silicon carbide adheres and deposits on the surface of the spring mold to form a silicon carbide ceramic layer by in-situ growth on the surface of the spring mold. The formed silicon carbide ceramic layer can not only prevent the components of the spring mold itself from entering the spring finished product, but also help to improve the quality of the subsequently formed spring finished product; moreover, the formed silicon carbide ceramic layer can also improve the physical and chemical compatibility between the spring mold and the fiber braid, so that the fiber braid can adapt to the thermal mismatch between the mold and the braid in all subsequent thermal processes, and can achieve self-release of internal stress during the cooling process of the thermal process, thereby reducing the process difficulty and preparation cost.

[0016] In some preferred embodiments of the present invention, when a silicon carbide ceramic layer is deposited on the surface of the spring mold, the process conditions of the chemical vapor deposition treatment are:

[0017] Under the pressure condition of 20Pa to 150Pa, the spring mold is heated to 1200℃ to 1300℃ and kept warm for 4h to 8h; then, an atmosphere containing a silicon carbide source is introduced and deposited for 4h to 12h, so that the silicon carbide source is converted into silicon carbide during the vapor deposition process and deposited on the spring mold to form a silicon carbide ceramic layer on the surface of the spring mold; the introduction of the silicon carbide source is stopped and the heat is kept warm for 1h to 2h to reduce the stress inside the workpiece and ensure that the spring mold does not undergo thermal deformation. Then the temperature is lowered to room temperature, i.e., a silicon carbide ceramic layer is formed on the surface of the spring mold to obtain a stabilized spring mold.

[0018] In some more preferred embodiments of the present invention, trichloromethylsilane is used as the silicon carbide source, that is, the atmosphere containing the silicon carbide source used in the present invention is a mixed gas of trichloromethylsilane, hydrogen and argon, wherein hydrogen is a carrier gas and argon is a diluent gas for dilution, so that trichloromethylsilane can be uniformly diffused and in-situ decomposed to generate silicon carbide at 1200°C to 1300°C under the synergistic effect of hydrogen and argon, so as to ensure that a silicon carbide ceramic layer can be formed on the surface of the spring mold. In some more preferred embodiments of the present invention, the flow ratio of trichloromethylsilane, hydrogen and argon is 1:3 to 5:10 to 12. Within this range, the ability of trichloromethylsilane to penetrate into the spring mold is the best, the rate of generating silicon carbide ceramics is good, and the microstructure of the generated silicon carbide ceramics is the best, which can ensure the comprehensive mechanical, physical and chemical properties of the material.

[0019] Step 3, preparation of spring braid:

[0020] A plurality of strands of silicon carbide fibers are combined and braided to obtain a fiber braided body; the fiber braided body is embedded in the stabilized spring mold and fixed to obtain a spring braided body.

[0021] The present invention does not specifically limit the number of strands of the silicon carbide fiber, and can be selected accordingly according to actual needs. For example, in some preferred embodiments of the present invention, the number of strands of the silicon carbide fiber is 2 to 6 strands.

[0022] In some preferred embodiments of the present invention, when performing weaving processing, the present invention preferably adopts any one of the weaving methods of three-dimensional four-directional, three-dimensional six-directional and two-dimensional circumferential for weaving processing, and the warp and weft weaving angles during weaving processing are 17°~38°, so that in the spring braided body formed by weaving, the fiber bundles in the cross section of the spring braided body are interconnected, and when the spring is subjected to axial tensile and compressive loads, the fibers in the cross section can constrain each other, effectively improving the torsional stiffness of the spring cross section, thereby improving the axial stiffness of the spring on a macro scale, and avoiding microstructural damage, falling off, peeling and other phenomena of the spring under large deformation conditions.

[0023] In some preferred embodiments of the present invention, in order to avoid the spring braid from moving in the stabilized spring mold during subsequent processing, resulting in the formed spring structure being inconsistent with the actual required structure, after the fiber braid is embedded in the stabilized spring mold, graphite bolts or bow clamps are used to fix the two ends of the fiber braid to the two ends of the stabilized spring mold.

[0024] Step 4, deposition of the interfacial phase layer:

[0025] In an atmosphere containing a boron nitride source, a layer of boron nitride is deposited inside and on the surface of the spring braid as an interface phase layer by using a chemical vapor deposition method to obtain a modified spring braid.

[0026] It should be noted that the present invention first uses chemical vapor deposition technology to deposit a layer of boron nitride inside and on the surface of the spring braid, that is, a layer of boron nitride is attached and deposited on the surface of the fiber monofilaments and fiber bundles inside the fiber braid, so that the formed boron nitride layer serves as an interface phase layer, thereby effectively improving the mechanical properties of the spring material such as toughness and strength, coordinating the torsional deformation of the cross-sectional fibers when the spring is stretched or compressed, and being able to effectively withstand neutron irradiation and oxidizing environments, thereby greatly improving the long-term stability of the spring during use.

[0027] In some preferred embodiments of the present invention, when depositing the interface phase layer, the temperature is raised to 680°C to 840°C under a pressure of 100Pa to 3000Pa, and then kept warm for 4h to 8h, which is equivalent to a heat treatment process with the furnace to reduce the stress inside the workpiece and ensure that the workpiece does not undergo thermal deformation. Subsequently, an atmosphere containing a boron nitride source is introduced and deposited for 24h to 36h, so that the boron nitride source forms boron nitride during the vapor deposition process, and the formed boron nitride is deposited inside and on the surface of the spring braid to form an interface phase layer. According to the different performance requirements of the spring, the above steps are performed once or twice to obtain workpieces with different mechanical properties, that is, a modified spring braid.

[0028] In some more preferred embodiments of the present invention, ammonia and boron trichloride are used together as boron nitride sources, that is, the atmosphere containing the boron nitride source used in the present invention is a mixed gas composed of argon, hydrogen, ammonia and boron trichloride, wherein ammonia and boron trichloride can react to produce boron nitride during the deposition process, thereby forming an interface phase layer inside and on the surface of the spring braid. And the flow ratio of argon, hydrogen, ammonia and boron trichloride is 1:5-8:10-15:10-15. Within this range, ammonia and boron trichloride have the best ability to penetrate into the workpiece, the rate of generating silicon nitride ceramics is better, and the microstructure of the generated silicon nitride ceramics is the best, which can ensure the comprehensive mechanical, physical and chemical properties of the material.

[0029] Step 5, deposition of ceramic matrix layer:

[0030] The modified spring braid is subjected to chemical vapor deposition treatment in an atmosphere containing a silicon carbide source to deposit a ceramic matrix layer on the surface of the interface phase layer, and then demoulding is performed to obtain a spring blank.

[0031] It should be noted that the present invention further deposits a layer of silicon carbide as a ceramic matrix layer on the surface of the interface phase layer, so that the formed ceramic matrix layer and the boron nitride are combined through heterogeneous materials to form an interface with moderate bonding strength, which plays a role in transferring loads, increasing toughness, improving strength, and alleviating fiber oxidation.

[0032] In some preferred embodiments of the present invention, when depositing the ceramic matrix layer, the temperature is raised to 1000°C to 1200°C under a pressure of 500Pa to 3000Pa, and then kept warm for 1h to 2h. Subsequently, an atmosphere containing a silicon carbide source is introduced, and the deposition is performed for 52h to 64h, so that the silicon carbide source forms silicon carbide during the vapor deposition process, and the silicon carbide gradually adheres to the surface of the interface phase layer, thereby forming a ceramic matrix layer. Then, the introduction of trichloromethylsilane is stopped, and the temperature is kept warm for 1h to 2h, and then the temperature is lowered to room temperature. According to the different performance requirements of the spring, the above steps are performed 4 to 8 times to achieve uniform generation of silicon carbide ceramics on the surface and inside of the spring, and then demolding is performed to obtain a spring blank with uniform performance.

[0033] In some more preferred embodiments of the present invention, trichloromethylsilane is used as the silicon carbide source, that is, the atmosphere containing the silicon carbide source used in the present invention is a mixed gas of trichloromethylsilane, hydrogen and argon, wherein hydrogen is a carrier gas and argon is a diluent gas for dilution, so that trichloromethylsilane can be uniformly diffused and in-situ decomposed to generate silicon carbide at 1000°C to 1200°C under the synergistic effect of hydrogen and argon, so as to ensure that a layer of silicon carbide can be formed on the surface of the interface phase layer, and the formed silicon carbide layer is used as the ceramic matrix layer. In some more preferred embodiments of the present invention, the flow ratio of trichloromethylsilane, hydrogen and argon is 1:5 to 15:15 to 25. Within this range, the ability of trichloromethylsilane to penetrate into the interface phase layer is the best, the rate of generating silicon carbide ceramics is good, and the microstructure of the generated silicon carbide ceramics is the best, which can ensure the comprehensive mechanical, physical and chemical properties of the material.

[0034] Step 6, formation of rare earth co-infiltration layer:

[0035] The spring blank is subjected to embedding infiltration treatment by adopting the embedding infiltration method, so as to form a rare earth co-infiltration layer on the surface of the ceramic matrix layer, thereby obtaining a stabilized spring blank.

[0036] It should be noted that, in the present invention, a rare earth co-infiltration layer is formed on the surface of the ceramic base layer, so that the formed rare earth co-infiltration layer can enhance the bonding strength with the ceramic layer.

[0037] In some preferred embodiments of the present invention, the raw materials for preparing the embedding agent used in the embedding infiltration treatment are composed of the following components in mass percentage: SiC 10% to 25%, CeO2 1% to 5%, Y2O3 4% to 6%, La2O3 0.5% to 2%, and the remainder is Al2O3, totaling 100%.

[0038] In some preferred embodiments of the present invention, the embedding infiltration treatment is carried out by the following steps:

[0039] The embedding agent is covered on the surface of the workpiece with a covering thickness of 0.5mm to 3mm to obtain an embedding mixture; the embedding mixture is heated to 1300°C to 1450°C at 5Pa to 150Pa, kept warm for 0.5h to 1.5h, and then cooled to room temperature to obtain the stabilized spring blank.

[0040] Step 7, formation of surface strengthening layer:

[0041] The carbide powder is dispersed in an organic solvent to obtain a coating slurry; the coating slurry is coated on the surface of the stabilized spring blank, and after drying, a chemical vapor deposition method is used to transform the coating slurry into a surface reinforcement layer to obtain a spring semi-finished product.

[0042] It should be noted that the present invention uses a coating slurry whose main component is carbide powder as a surface reinforcement material. After applying the coating slurry to the surface of a stabilized spring blank, the coating slurry is solidified by drying, and then treated by chemical vapor deposition, so that the carbides in the solidified carbide powder form a surface reinforcement layer whose main component is a carbide layer on the surface of the rare earth co-diffusion layer, so that the rare earth co-diffusion layer is ceramicized by the formed carbide layer, and the bonding strength with the rare earth co-diffusion layer is improved, so that the fatigue resistance and structural integrity of the formed spring product under high temperature conditions are greatly improved, and the rebound retention rate of the spring after being subjected to repeated tensile and compressive loads is significantly improved. At the same time, by preparing a ceramic reinforcement layer on the surface of the spring, the phenomena of slag falling and block falling that may occur during long-term use are eliminated.

[0043] In some preferred embodiments of the present invention, the carbide powder is one or more of silicon carbide powder, silicon carbide whisker and zirconium carbide powder.

[0044] In some preferred embodiments of the present invention, the organic solvent is one or more of polycarbosilane, xylene and polypropylene alcohol.

[0045] In some preferred embodiments of the present invention, the usage ratio of the carbide powder to the organic solvent is 1 mg: 5 mL to 25 mL to obtain a slurry with moderate viscosity, so as to achieve smooth penetration of the slurry in the subsequent coating process and enhance the bonding strength between the surface reinforcement layer and the spring body.

[0046] In some preferred embodiments of the present invention, the sizing amount of the coating slurry is 30 g / m 2 ~50g / m 2 .

[0047] In some preferred embodiments of the present invention, when preparing the surface strengthening layer, the process conditions of the chemical vapor deposition treatment are: under the pressure condition of 500Pa~3000Pa, after heating to 1000℃~1200℃, keep warm for 1h~2h. Then, introduce an atmosphere containing a silicon carbide source and deposit for 52h~64h, so that the silicon carbide source forms silicon carbide during the vapor deposition process, and the silicon carbide gradually adheres to the surface of the rare earth co-diffusion layer to form a ceramic matrix layer. Then, stop introducing trichloromethylsilane, continue to keep warm for 1h~2h, and then cool to room temperature. According to the different performance requirements of the spring, perform the above steps 4 to 8 times to achieve further uniform generation of a surface strengthening layer on the surface of the spring surface and the surface of the rare earth co-diffusion layer inside, and obtain a spring semi-finished product with uniform performance.

[0048] In some more preferred embodiments of the present invention, trichloromethylsilane is used as the silicon carbide source, that is, the atmosphere containing the silicon carbide source used in the present invention is a mixed gas of trichloromethylsilane, hydrogen and argon, wherein hydrogen is a carrier gas and argon is a diluent gas for dilution, so that trichloromethylsilane can be uniformly diffused and in-situ decomposed to generate silicon carbide at 1000°C to 1200°C under the synergistic effect of hydrogen and argon, so as to ensure that a silicon carbide ceramic layer can be formed on the surface of the rare earth co-diffusion layer. In some more preferred embodiments of the present invention, the flow ratio of trichloromethylsilane, hydrogen and argon is 1:5 to 15:15 to 25. Within this range, the ability of trichloromethylsilane to penetrate into the rare earth co-diffusion layer is the best, the rate of generating silicon carbide ceramics is good, and the microstructure of the generated silicon carbide ceramics is the best, which can ensure the comprehensive mechanical, physical and chemical properties of the material.

[0049] Step 8, polishing:

[0050] The semi-finished spring product is polished to obtain the ceramic composite material spring.

[0051] It should be noted that the present invention further performs a grinding process on the semi-finished spring product to remove defects and impurities on the surface of the semi-finished spring product through the grinding process to obtain the ceramic composite material spring.

[0052] In some preferred embodiments of the present invention, during the grinding process, a sandblaster or sandpaper is used for grinding, and the grinding process is performed until the surface is smooth and free of scum and burrs, which is considered to achieve the removal of defects and impurities on the surface of the semi-finished spring.

[0053] The present invention also provides a ceramic composite material spring prepared by the above preparation method.

[0054] It should be noted that the ceramic composite material spring prepared by the present invention uses continuous silicon carbide ceramic fiber as the spring matrix, on which are the interface phase layer, ceramic matrix layer, rare earth co-infiltration layer and surface reinforcement layer in sequence. Among them, the continuous silicon carbide ceramic fiber is obtained by twisting and three-dimensional multi-directional weaving, which can maintain good internal cross-sectional constraints under large deformation and fatigue conditions of the spring, thereby ensuring the rebound characteristics of the spring. The infiltrated rare earth components and silicon carbide ceramics are tightly combined with the fiber braid and the surface ceramic reinforcement layer to prevent the spring from cracking, peeling and the like when used for a long time at high temperature. The ceramic composite material spring prepared by the present invention has good stability in a neutron irradiation environment and can withstand an inert or aerobic environment of 1350°C for a long time.

[0055] Compared with the prior art, the present invention has the following beneficial effects:

[0056] The present invention first selects a corresponding spring mold according to the structure of the required spring. Then, the spring mold is subjected to chemical vapor deposition treatment to deposit a layer of silicon carbide ceramic layer on the surface of the spring mold, so as to prevent the components of the spring mold itself from entering the finished spring through the silicon carbide ceramic layer, and at the same time improve the physical and chemical compatibility of the spring mold and the fiber braid, thereby reducing the process difficulty and preparation cost. Then, a plurality of strands of silicon carbide fibers are braided into a fiber braid by a braiding method, and then embedded in the stabilized spring mold, so that the fiber bundles in the obtained spring braid are interconnected, and when the spring is subjected to axial tension and compression loads, the fibers in the cross section can be constrained to each other, effectively improving the torsional stiffness of the spring cross section, thereby macroscopically improving the axial stiffness of the spring, and avoiding microstructural damage, block drop, peeling, and other phenomena of the spring under large deformation conditions. In an atmosphere containing a boron nitride source, the spring braid is subjected to a chemical vapor deposition treatment to deposit an interface phase layer inside and on the surface of the spring braid, so that the mechanical properties such as toughness and strength of the spring material are effectively improved through the formed interface phase layer, the torsional deformation of the cross-sectional fiber when the spring is stretched or compressed is coordinated, and it can effectively withstand neutron irradiation and oxidizing environments, thereby greatly improving the long-term stability of the spring when in use. In an atmosphere containing a silicon carbide source, the modified spring braid is subjected to a chemical vapor deposition treatment to deposit a ceramic matrix layer on the surface of the interface phase layer. Then, a rare earth co-infiltration layer and a carbide layer are formed in sequence, so that the rare earth co-infiltration layer is ceramicized through the formed carbide layer, and the bonding strength with the rare earth co-infiltration layer is improved, so that the fatigue resistance and structural integrity of the formed spring product under high temperature conditions are greatly improved, and the spring rebound retention rate after being subjected to repeated tensile and compressive loads is significantly improved. At the same time, by preparing a ceramic reinforcement layer on the surface of the spring, the phenomenon of slag and block falling that may occur during long-term use is eliminated. Finally, the defects and impurities on the surface of the semi-finished spring are removed by grinding to obtain the ceramic composite material spring.

[0057] The preparation process of the present invention has low operating difficulty. Through weaving, infiltration, surface deposition and other processes, the organic combination of various material components in the spring is achieved, the bonding strength between the fiber and each layer is improved, and the stabilization of the mechanical properties of the spring under high temperature, neutron irradiation environment and oxidative atmosphere is achieved.

[0058] The present invention adopts a technical process of first ceramicizing the fiber braid and preparing a rare earth co-infiltration layer, and then ceramicizing. Since the rare earth co-infiltration layer infiltrated into the braid can improve the bonding strength between it and the ceramic layer, after ceramicization, the fatigue resistance and structural integrity of the spring under high temperature conditions are greatly improved, and the spring rebound retention rate after repeated tensile and compressive loads is significantly improved. At the same time, by preparing a ceramic reinforcement layer on the surface of the spring, the phenomenon of slag and block falling that may occur during long-term use is eliminated. The combination of the above multiple processes effectively improves the comprehensive performance of the spring, such as high temperature resistance, fatigue resistance, and long-term stability, prolongs the service life of the spring, and reduces the risk of structural failure.

[0059] The present invention first implements a stabilization treatment process on the mold, and then adopts parameters with special braiding angles to prepare the braid. The organic combination of the two enables the fiber braid to adapt to the thermal mismatch between the mold and the braid in all subsequent thermal processes, and can achieve self-release of internal stress during the cooling process of the thermal process. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] Figure 1 It is a process flow chart of the present invention.

[0061] Figure 2 This is a physical picture of the spring of Example 1 of the present invention. DETAILED DESCRIPTION

[0062] The technical solutions in the embodiments of the present invention will be described clearly and completely below.

[0063] Example 1

[0064] This embodiment provides a ceramic composite material spring, which is manufactured by the following steps:

[0065] Step 1, select the mold:

[0066] 1.1) In order to prepare a spring for a control rod buffer structure of a small gas-cooled nuclear reactor, this embodiment uses a three-dimensional software to design a mold model with a spiral groove of corresponding size according to the geometric parameters of the spring: wire diameter of 3 mm, maximum outer diameter of 25 mm, pitch of 12 mm, and total height of 50 mm.

[0067] 1.2) According to the obtained mold model, high-purity graphite is used as raw material, and mechanical processing is adopted to complete the mold processing to obtain a spring mold.

[0068] Step 2, stabilization of the spring mold:

[0069] 2.1) The spring mold obtained in the above steps is placed in a chemical vapor deposition furnace, heated to 1200°C at a pressure of 20 Pa and kept at this temperature for 4 hours.

[0070] 2.2) A mixed gas of trichloromethylsilane, hydrogen and argon is introduced, and the flow ratio of trichloromethylsilane, hydrogen and argon is 1:3:10, and the deposition is carried out for 4 hours.

[0071] 2.3) Keep the temperature at 1200°C for 2 h, then cool to room temperature to obtain a stabilized spring mold.

[0072] Step 3, preparation of spring braid:

[0073] 3.1) After 6 strands of silicon carbide fibers are combined, a three-dimensional four-directional weaving method is adopted, and the warp and weft weaving angles are 17° to obtain a fiber braided body.

[0074] 3.2) The fiber braid is embedded in situ along the spiral groove of the mold, and the two ends of the spiral braid are fixed to the two ends of the mold using graphite bolts to obtain a spring braid.

[0075] Step 4, deposition of the interfacial phase layer:

[0076] 4.1) Place the mold with the spring braid in a chemical vapor infiltration furnace, heat it to 680°C at a pressure of 100 Pa, and keep it at this temperature for 4 hours.

[0077] 4.2) A mixed gas of argon, hydrogen, ammonia and boron trichloride was introduced with a flow ratio of argon, hydrogen, ammonia and boron trichloride of 1:5:10:10, and the deposition was continued for 24 hours.

[0078] 4.3) The above 4.1) and 4.2) are regarded as one cycle, and this cycle is performed twice to prepare an interface phase layer with a thickness of 650 nm on the surface and inside of the fiber braid.

[0079] Step 5, deposition of ceramic matrix layer:

[0080] 5.1) Under a pressure of 500 Pa, heat to 1000°C and keep warm for 2 hours.

[0081] 5.2) A mixed gas of trichloromethylsilane, hydrogen and argon was introduced with a flow ratio of trichloromethylsilane, hydrogen and argon being 1:5:15, and the deposition was performed for 52 hours.

[0082] 5.3) Keep at 1000℃ for 2h and then cool to room temperature.

[0083] 5.4) Treat 5.1), 5.2) and 5.3) as a loop and execute the loop 8 times.

[0084] 5.5) Remove the fiber braid from the mold to obtain a spring blank.

[0085] Step 6, formation of rare earth co-infiltration layer:

[0086] 6.1) According to the following mass percentage ratio, weigh the corresponding mass of SiC, CeO2, Y2O3, La2O3 and Al2O3 and mix them evenly to prepare an embedding agent:

[0087] SiC 25%, CeO 25%, Y2O 34%, La2O3 0.5%, and the balance is Al2O3.

[0088] 6.2) The embedding agent prepared in 6.1) above is used to embed the spring blank prepared above, with a covering thickness of 0.5 mm, to obtain an embedding mixture.

[0089] 6.3) The embedded mixture obtained in 6.2) was heated to 1300°C at 150 Pa, kept at this temperature for 1.5 hours, and then cooled to room temperature to obtain a stabilized spring blank.

[0090] Step 7, formation of surface strengthening layer:

[0091] 7.1) Silicon carbide whiskers, polycarbosilane and xylene are mixed in a mass ratio of 4:1:15 to obtain a coating slurry.

[0092] 7.2) The above coating slurry was mixed at 30 g / m 2 The sizing amount is evenly applied on the surface of the stabilized spring blank obtained above, and then placed in a fume hood to dry for 2 hours.

[0093] 7.3) Place the dried product of 7.2) in a chemical vapor deposition apparatus, raise the temperature to 1000°C at a pressure of 500 Pa, and keep it at this temperature for 2 hours.

[0094] 7.4) A mixed gas of trichloromethylsilane, hydrogen and argon was introduced with a flow ratio of trichloromethylsilane, hydrogen and argon being 1:5:15, and the deposition was continued for 52 hours.

[0095] 7.5) Keep the temperature at 1000℃ for 2 h and then cool to room temperature.

[0096] 7.6) Take 7.3), 7.4) and 7.5) as one cycle, and perform this cycle 8 times to obtain a semi-finished spring.

[0097] Step 8, polishing:

[0098] The burrs and attachments on the surface of the semi-finished spring obtained in the above steps are removed by a sandblasting machine to obtain a finished spring, that is, a ceramic composite material spring of this embodiment, and the actual product is as follows: Figure 2 shown.

[0099] Example 2

[0100] This embodiment provides a ceramic composite material spring, which is manufactured by the following steps:

[0101] Step 1, select the mold:

[0102] 1.1) In order to prepare aerospace engine accessory buffer springs, this embodiment uses 3D software to design a mold model with a spiral groove of corresponding size according to the geometric parameters of the spring: wire diameter of 5 mm, maximum outer diameter of 22 mm, pitch of 8 mm, and total height of 33 mm.

[0103] 1.2) According to the obtained mold model, high-purity graphite is used as raw material, and mechanical processing is adopted to complete the mold processing to obtain a spring mold.

[0104] Step 2, stabilization of the spring mold:

[0105] 2.1) The spring mold obtained in the above steps is placed in a chemical vapor deposition furnace, heated to 1300° C. at a pressure of 150 Pa and kept at this temperature for 8 h.

[0106] 2.2) A mixed gas of trichloromethylsilane, hydrogen and argon was introduced with a flow ratio of trichloromethylsilane, hydrogen and argon being 1:5:12, and the deposition was carried out for 12 hours.

[0107] 2.3) Keep the temperature at 1300°C for 1 hour, then cool to room temperature to obtain a stabilized spring mold.

[0108] Step 3, preparation of spring braid:

[0109] 3.1) After two strands of silicon carbide fibers are combined, a three-dimensional four-directional weaving method is adopted, and the warp and weft weaving angles are 38° to obtain a fiber braided body.

[0110] 3.2) The fiber braid is embedded in situ along the spiral groove of the mold, and graphite bolts are used to fix the two ends of the spiral braid to the two ends of the mold to obtain a spring braid.

[0111] Step 4, deposition of the interfacial phase layer:

[0112] 4.1) Place the mold with the spring braid in a chemical vapor infiltration furnace, heat it to 840°C at a pressure of 3000 Pa, and keep it at this temperature for 8 hours.

[0113] 4.2) A mixed gas of argon, hydrogen, ammonia and boron trichloride was introduced with a flow ratio of argon, hydrogen, ammonia and boron trichloride of 1:8:15:15. The mixture was deposited for 36 hours to obtain an interfacial phase layer with a thickness of 350 nm on the surface and inside of the fiber braid.

[0114] Step 5, deposition of ceramic matrix layer:

[0115] 5.1) Under the condition of pressure of 3000Pa, heat to 1200℃ and keep it at this temperature for 1h.

[0116] 5.2) A mixed gas of trichloromethylsilane, hydrogen and argon was introduced with a flow ratio of trichloromethylsilane, hydrogen and argon being 1:15:25, and the deposition was performed for 64 hours.

[0117] 5.3) Keep the temperature at 1200℃ for 1 hour and then cool to room temperature.

[0118] 5.4) Treat 5.1), 5.2) and 5.3) as a loop and execute the loop 4 times.

[0119] 5.5) Remove the fiber braid from the mold to obtain a spring blank.

[0120] Step 6, formation of rare earth co-infiltration layer:

[0121] 6.1) According to the following mass percentage ratio, weigh the corresponding mass of SiC, CeO2, Y2O3, La2O3 and Al2O3 and mix them evenly to prepare an embedding agent:

[0122] SiC 10%, CeO2 1%, Y2O3 6%, La2O3 2%, and the balance is Al2O3.

[0123] 6.2) The embedding agent prepared in 6.1) above is used to embed the spring blank prepared above, with a covering thickness of 3 mm, to obtain an embedding mixture.

[0124] 6.3) The embedded mixture obtained in 6.2) was heated to 1450°C at 5 Pa, kept at this temperature for 0.5 h, and then cooled to room temperature to obtain a stabilized spring blank.

[0125] Step 7, formation of surface strengthening layer:

[0126] 7.1) Silicon carbide powder, zirconium carbide powder, polycarbosilane and xylene are mixed in a mass ratio of 2:4:1:12 to obtain a coating slurry.

[0127] 7.2) The above coating slurry was mixed at 50 g / m 2 The sizing amount is evenly applied on the surface of the stabilized spring blank obtained above, and then placed in a fume hood to dry for 24 hours.

[0128] 7.3) Place the dried product of 7.2) in a chemical vapor deposition apparatus, raise the temperature to 1200°C at a pressure of 3000 Pa, and keep the temperature for 1 hour.

[0129] 7.4) A mixed gas of trichloromethylsilane, hydrogen and argon was introduced with a flow ratio of trichloromethylsilane, hydrogen and argon being 1:15:25, and the deposition was continued for 64 hours.

[0130] 7.5) Keep the temperature at 1200℃ for 1h and then cool to room temperature.

[0131] 7.6) Take 7.3), 7.4) and 7.5) as one cycle, and perform this cycle 4 times to prepare the surface reinforcement layer and obtain a semi-finished spring.

[0132] Step 8, polishing:

[0133] A sandblasting machine is used to remove burrs and attachments on the surface of the semi-finished spring obtained in the above steps to obtain a finished spring, namely the ceramic composite material spring of this embodiment.

[0134] Example 3

[0135] This embodiment provides a ceramic composite material spring, which is manufactured by the following steps:

[0136] Step 1, select the mold:

[0137] 1.1) In order to prepare aerospace engine accessory buffer springs, this embodiment uses 3D software to design a mold model with a spiral groove of corresponding size according to the geometric parameters of the spring: wire diameter of 5 mm, maximum outer diameter of 22 mm, pitch of 8 mm, and total height of 33 mm.

[0138] 1.2) According to the obtained mold model, high-purity graphite is used as raw material, and mechanical processing is adopted to complete the mold processing to obtain a spring mold.

[0139] Step 2, stabilization of the spring mold:

[0140] 2.1) The spring mold obtained in the above steps is placed in a chemical vapor deposition furnace, heated to 1250° C. at a pressure of 80 Pa and kept at this temperature for 6 hours.

[0141] 2.2) A mixed gas of trichloromethylsilane, hydrogen and argon is introduced, and the flow ratio of trichloromethylsilane, hydrogen and argon is 1:4:11, and the deposition is carried out for 8 hours.

[0142] 2.3) Keep the temperature at 1250°C for 1.5 h, then cool to room temperature to obtain a stabilized spring mold.

[0143] Step 3, preparation of spring braid:

[0144] 3.1) After 4 strands of silicon carbide fibers are combined, a three-dimensional four-directional weaving method is adopted, and the warp and weft weaving angles are 27° to obtain a fiber braided body.

[0145] 3.2) The fiber braid is embedded in situ along the spiral groove of the mold, and graphite bolts are used to fix the two ends of the spiral braid to the two ends of the mold to obtain a spring braid.

[0146] Step 4, deposition of the interfacial phase layer:

[0147] 4.1) Place the mold with the spring braid in a chemical vapor infiltration furnace, heat it to 760°C at a pressure of 1500 Pa, and keep it at this temperature for 6 hours.

[0148] 4.2) A mixed gas of argon, hydrogen, ammonia and boron trichloride was introduced with a flow ratio of argon, hydrogen, ammonia and boron trichloride of 1:7:13:13, and the mixture was deposited for 30 hours to obtain an interface phase layer on the surface and inside of the fiber braid.

[0149] Step 5, deposition of ceramic matrix layer:

[0150] 5.1) Under the condition of pressure of 1700Pa, heat to 1100℃ and keep it warm for 1.5h.

[0151] 5.2) A mixed gas of trichloromethylsilane, hydrogen and argon was introduced with a flow ratio of trichloromethylsilane, hydrogen and argon being 1:10:20, and the deposition was performed for 58 hours.

[0152] 5.3) Keep the temperature at 1100℃ for 1.5h and then cool to room temperature.

[0153] 5.4) Treat 5.1), 5.2) and 5.3) as one loop and execute the loop 6 times.

[0154] 5.5) Remove the fiber braid from the mold to obtain a spring blank.

[0155] Step 6, formation of rare earth co-infiltration layer:

[0156] 6.1) According to the following mass percentage ratio, weigh the corresponding mass of SiC, CeO2, Y2O3, La2O3 and Al2O3 and mix them evenly to prepare an embedding agent:

[0157] SiC 17.5%, CeO23%, Y2O35%, La2O31%, and the balance is Al2O3.

[0158] 6.2) The embedding agent prepared in 6.1) above is used to embed the spring blank prepared above, with a covering thickness of 1.5 mm, to obtain an embedding mixture.

[0159] 6.3) The embedded mixture obtained in 6.2) was heated to 1370°C at 80 Pa, kept at this temperature for 1 hour, and then cooled to room temperature to obtain a stabilized spring blank.

[0160] Step 7, formation of surface strengthening layer:

[0161] 7.1) Silicon carbide powder, zirconium carbide powder, polycarbosilane and xylene are mixed in a mass ratio of 2:4:1:12 to obtain a coating slurry.

[0162] 7.2) The above coating slurry was mixed at 40 g / m 2 The sizing amount is evenly applied on the surface of the stabilized spring blank obtained above, and then placed in a fume hood to dry for 24 hours.

[0163] 7.3) Place the dried product of 7.2) in a chemical vapor deposition apparatus, raise the temperature to 1100°C at a pressure of 1700 Pa, and keep the temperature for 1.5 hours.

[0164] 7.4) A mixed gas of trichloromethylsilane, hydrogen and argon was introduced with a flow ratio of trichloromethylsilane, hydrogen and argon being 1:10:20, and the deposition was continued for 58 hours.

[0165] 7.5) Keep the temperature at 1100℃ for 1.5h and then cool to room temperature.

[0166] 7.6) Take 7.3), 7.4) and 7.5) as one cycle, and perform this cycle 6 times to prepare the surface reinforcement layer and obtain a semi-finished spring.

[0167] Step 8, polishing:

[0168] A sandblasting machine is used to remove burrs and attachments on the surface of the semi-finished spring obtained in the above steps to obtain a finished spring, namely the ceramic composite material spring of this embodiment.

[0169] Comparative Example 1

[0170] This comparative example provides a ceramic composite spring, which is prepared by the following steps:

[0171] Step 1, select the mold:

[0172] 1.1) The geometric parameters of this comparative spring are: wire diameter is 3 mm, maximum outer diameter is 25 mm, pitch is 12 mm, total height is 50 mm, and a mold model with a spiral groove of corresponding size is designed using 3D software.

[0173] 1.2) According to the obtained mold model, high-purity graphite is used as raw material, and mechanical processing is adopted to complete the mold processing to obtain a spring mold.

[0174] Step 2, stabilization of the spring mold:

[0175] 2.1) The spring mold obtained in the above steps is placed in a chemical vapor deposition furnace, heated to 1200°C at a pressure of 20 Pa and kept at this temperature for 4 hours.

[0176] 2.2) A mixed gas of trichloromethylsilane, hydrogen and argon is introduced, and the flow ratio of trichloromethylsilane, hydrogen and argon is 1:3:10, and the deposition is carried out for 4 hours.

[0177] 2.3) Keep the temperature at 1200°C for 2 h, then cool to room temperature to obtain a stabilized spring mold.

[0178] Step 3, preparation of spring braid:

[0179] 3.1) After 6 strands of carbon fiber are combined, a three-dimensional four-directional weaving method is adopted, and the warp and weft weaving angles are 22° to obtain a fiber braided body.

[0180] 3.2) The fiber braid is embedded in situ along the spiral groove of the mold, and the two ends of the spiral braid are fixed to the two ends of the mold using graphite bolts to obtain a spring braid.

[0181] Step 4, deposition of the interfacial phase layer:

[0182] 4.1) Place the mold with the spring braid in a chemical vapor infiltration furnace, heat it to 680°C at a pressure of 100 Pa, and keep it at this temperature for 4 hours.

[0183] 4.2) Using propane as the carbon source, a mixed gas of argon and propane was introduced with a flow ratio of argon to propane of 4:1, and the deposition was carried out for 24 hours.

[0184] 4.3) The above 4.1) and 4.2) are regarded as one cycle, and the cycle is performed twice to prepare a layer of pyrolytic carbon on the surface and inside of the fiber braided body to form an interface phase layer.

[0185] Step 5, deposition of ceramic matrix layer:

[0186] 5.1) Under a pressure of 500 Pa, heat to 1000°C and keep warm for 2 hours.

[0187] 5.2) A mixed gas of trichloromethylsilane, hydrogen and argon was introduced with a flow ratio of trichloromethylsilane, hydrogen and argon being 1:5:15, and the deposition was performed for 52 hours.

[0188] 5.3) Keep at 1000℃ for 2h and then cool to room temperature.

[0189] 5.4) Treat 5.1), 5.2) and 5.3) as one loop and execute the loop 6 times.

[0190] 5.5) Remove the fiber braid from the mold to obtain a semi-finished spring.

[0191] Step 6, polishing:

[0192] A sandblasting machine is used to remove burrs and attachments on the surface of the semi-finished spring obtained in the above steps to obtain a finished spring, namely, the ceramic composite material spring of this comparative example.

[0193] Comparative Example 2

[0194] This comparative example provides a ceramic composite spring, which is prepared by the following steps:

[0195] Step 1, select the mold:

[0196] 1.1) This comparative example uses 3D software to design a mold model with a spiral groove of corresponding size based on the geometric parameters of the spring: wire diameter is 3 mm, maximum outer diameter is 25 mm, pitch is 12 mm, and total height is 50 mm.

[0197] 1.2) According to the obtained mold model, high-purity graphite is used as raw material, and mechanical processing is adopted to complete the mold processing to obtain a spring mold.

[0198] Step 2, stabilization of the spring mold:

[0199] 2.1) The spring mold obtained in the above steps is placed in a chemical vapor deposition furnace, heated to 1200°C at a pressure of 20 Pa and kept at this temperature for 4 hours.

[0200] 2.2) A mixed gas of trichloromethylsilane, hydrogen and argon is introduced, and the flow ratio of trichloromethylsilane, hydrogen and argon is 1:3:10, and the deposition is carried out for 4 hours.

[0201] 2.3) Keep the temperature at 1200°C for 2 h, then cool to room temperature to obtain a stabilized spring mold.

[0202] Step 3, preparation of spring braid:

[0203] 3.1) After a strand of silicon carbide fiber is combined, a three-dimensional four-directional weaving method is adopted, and the warp and weft weaving angles are 15° to obtain a fiber braided body.

[0204] 3.2) The fiber braid is embedded in situ along the spiral groove of the mold, and the two ends of the spiral braid are fixed to the two ends of the mold using graphite bolts to obtain a spring braid.

[0205] Step 4, deposition of the interfacial phase layer:

[0206] 4.1) Place the mold with the spring braid in a chemical vapor infiltration furnace, heat it to 680°C at a pressure of 100 Pa, and keep it at this temperature for 4 hours.

[0207] 4.2) A mixed gas of argon, hydrogen, ammonia and boron trichloride was introduced with a flow ratio of argon, hydrogen, ammonia and boron trichloride of 1:5:10:10, and the deposition was continued for 24 hours.

[0208] 4.3) The above 4.1) and 4.2) are regarded as one cycle, and this cycle is performed twice to prepare an interface phase layer with a thickness of 650 nm on the surface and inside of the fiber braid.

[0209] Step 5, deposition of ceramic matrix layer:

[0210] 5.1) Under a pressure of 500 Pa, heat to 1000°C and keep warm for 2 hours.

[0211] 5.2) A mixed gas of trichloromethylsilane, hydrogen and argon was introduced with a flow ratio of trichloromethylsilane, hydrogen and argon being 1:5:15, and the deposition was performed for 52 hours.

[0212] 5.3) Keep at 1000℃ for 2h and then cool to room temperature.

[0213] 5.4) Treat 5.1), 5.2) and 5.3) as a loop and execute the loop 9 times.

[0214] 5.5) Remove the fiber braid from the mold to obtain a spring blank.

[0215] Step 6: Formation of surface strengthening layer:

[0216] 6.1) Silicon carbide whiskers, polycarbosilane and xylene are mixed in a mass ratio of 4:1:15 to obtain a coating slurry.

[0217] 6.2) The above coating slurry was mixed at 75g / m 2 The sizing amount is evenly applied on the surface of the spring blank obtained above, and then placed in a fume hood to dry for 2 hours.

[0218] 6.3) Place the dried product of 6.2) in a chemical vapor deposition apparatus, raise the temperature to 1000°C at a pressure of 500 Pa, and keep the temperature for 2 hours.

[0219] 6.4) A mixed gas of trichloromethylsilane, hydrogen and argon was introduced with a flow ratio of trichloromethylsilane, hydrogen and argon being 1:5:15, and the deposition was continued for 52 hours.

[0220] 6.5) Keep the temperature at 1000℃ for 2 h and then cool to room temperature.

[0221] 6.6) Take 6.3), 6.4) and 6.5) as one cycle, and perform this cycle 8 times to obtain a semi-finished spring.

[0222] Step 7, polishing:

[0223] A sandblasting machine is used to remove burrs and attachments on the surface of the semi-finished spring obtained in the above steps to obtain a finished spring, namely, the ceramic composite material spring of this comparative example.

[0224] Comparative Example 3

[0225] This comparative example provides a ceramic composite spring, which is prepared by the following steps:

[0226] Step 1, select the mold:

[0227] 1.1) This comparative example uses 3D software to design a mold model with a spiral groove of corresponding size based on the geometric parameters of the spring: wire diameter is 3 mm, maximum outer diameter is 25 mm, pitch is 12 mm, and total height is 50 mm.

[0228] 1.2) According to the obtained mold model, high-purity graphite is used as raw material, and mechanical processing is adopted to complete the mold processing to obtain a spring mold.

[0229] Step 2, stabilization of the spring mold:

[0230] 2.1) The spring mold obtained in the above steps is placed in a chemical vapor deposition furnace, heated to 1200°C at a pressure of 20 Pa and kept at this temperature for 4 hours.

[0231] 2.2) A mixed gas of trichloromethylsilane, hydrogen and argon is introduced, and the flow ratio of trichloromethylsilane, hydrogen and argon is 1:3:10, and the deposition is carried out for 4 hours.

[0232] 2.3) Keep the temperature at 1200°C for 2 h, then cool to room temperature to obtain a stabilized spring mold.

[0233] Step 3, preparation of spring braid:

[0234] 3.1) After 4 strands of silicon carbide fibers are combined, a three-dimensional four-directional weaving method is adopted, and the warp and weft weaving angles are 22° to obtain a fiber braided body.

[0235] 3.2) The fiber braid is embedded in situ along the spiral groove of the mold, and the two ends of the spiral braid are fixed to the two ends of the mold using graphite bolts to obtain a spring braid.

[0236] Step 4, deposition of the interfacial phase layer:

[0237] 4.1) Place the mold with the spring braid in a chemical vapor infiltration furnace, heat it to 680°C at a pressure of 100 Pa, and keep it at this temperature for 4 hours.

[0238] 4.2) Using propane as the carbon source, a mixed gas of argon and propane was introduced with a flow ratio of argon to propane of 4:1, and the deposition was carried out for 24 hours.

[0239] 4.3) The above 4.1) and 4.2) are regarded as one cycle, and the cycle is performed twice to prepare an interface phase layer of a pyrolytic carbon layer on the surface and inside of the fiber braided body.

[0240] Step 5, deposition of ceramic matrix layer:

[0241] 5.1) Under a pressure of 500 Pa, heat to 1000°C and keep warm for 2 hours.

[0242] 5.2) A mixed gas of trichloromethylsilane, hydrogen and argon was introduced with a flow ratio of trichloromethylsilane, hydrogen and argon being 1:5:15, and the deposition was performed for 52 hours.

[0243] 5.3) Keep at 1000℃ for 2h and then cool to room temperature.

[0244] 5.4) Treat 5.1), 5.2) and 5.3) as a loop and execute the loop three times.

[0245] 5.5) Remove the fiber braid from the mold to obtain a spring blank.

[0246] Step 6: Formation of surface strengthening layer:

[0247] 6.1) Silicon carbide whiskers, polycarbosilane and xylene are mixed in a mass ratio of 4:1:15 to obtain a coating slurry.

[0248] 6.2) The above coating slurry was mixed at 10 g / m 2 The sizing amount is evenly applied on the surface of the stabilized spring blank obtained above, and then placed in a fume hood to dry for 2 hours.

[0249] 6.3) Place the dried product of 6.2) in a chemical vapor deposition apparatus, raise the temperature to 1000°C at a pressure of 500 Pa, and keep the temperature for 2 hours.

[0250] 6.4) A mixed gas of trichloromethylsilane, hydrogen and argon was introduced with a flow ratio of trichloromethylsilane, hydrogen and argon being 1:5:15, and the deposition was continued for 52 hours.

[0251] 6.5) Keep the temperature at 1000℃ for 2 h and then cool to room temperature.

[0252] 6.6) Take 6.3), 6.4) and 6.5) as one cycle, and perform this cycle 8 times to obtain a semi-finished spring.

[0253] Step 7, polishing:

[0254] A sandblasting machine is used to remove burrs and attachments on the surface of the semi-finished spring obtained in the above steps to obtain a finished spring, namely, the ceramic composite material spring of this comparative example.

[0255] In order to distinguish the above-mentioned embodiments and comparative examples, the main parameters of the preparation methods of the above-mentioned embodiments 1 to 3 and comparative examples 1 to 3 are summarized as described in Table 1.

[0256] Table 1 Main parameters of the preparation methods of Examples 1-3 and Comparative Examples 1-3

[0257]

[0258] Experimental Section

[0259] (I) Stiffness test

[0260] The present invention refers to the test method in GJB 6476 "Test method for compression properties of continuous fiber reinforced ceramic matrix composite materials at room temperature" and tests the stiffness of the ceramic composite springs of Examples 1 to 3 and Comparative Examples 1 to 3 respectively. The test results are shown in Table 2.

[0261] Table 2 Stiffness test results of ceramic composite springs

[0262] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Stiffness 28N / mm 33N / mm 25N / mm 2.2N / mm 15N / mm 21N / mm

[0263] It can be seen from the test results in Table 1 that the stiffness of Examples 1 to 3 is significantly improved compared to the carbon fiber reinforced carbon-based composite spring of Comparative Example 1. The stiffness of the ceramic composite spring of Example 1 is 28 N / mm, the stiffness of the ceramic composite spring of Example 2 is 33 N / mm, and the stiffness of the ceramic composite spring of Example 3 is 25 N / mm. By comparing the stiffness of Example 1 with Comparative Examples 1 to 3, it can be seen that the stiffness of Example 1 is significantly improved compared to Comparative Examples 1 to 3.

[0264] (II) Spring rebound performance test

[0265] The present invention refers to the test method in GJB 6476 "Test method for room temperature compression performance of continuous fiber reinforced ceramic matrix composite materials", and conducts room temperature compression performance tests on the resilience of the ceramic composite springs of Examples 1 to 3 and Comparative Examples 1 to 3, respectively. After repeated compression to the limit height 1000 times and unloading, the length of the spring is tested, and the degree of change in the spring length, that is, the rebound retention rate of the spring is used to evaluate the rebound performance of the spring, and the obtained spring rebound retention rate results are summarized as shown in Table 3.

[0266] Among them, the spring rebound retention rate = the length of the spring after the test / the original length of the spring × 100%.

[0267] Table 3 Rebound performance test results of ceramic composite springs

[0268] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Stiffness 28N / mm 33N / mm 25N / mm 2.2N / mm 15N / mm 21N / mm Rebound retention rate 98% 97% 99% 88% 95% 96%

[0269] It can be seen from the test results in Table 3 that the rebound performance of Examples 1 to 3 is significantly improved compared to the carbon fiber reinforced carbon-based composite spring of Comparative Example 1. The rebound retention rate of the ceramic composite spring of Example 1 is 98%, the rebound retention rate of the ceramic composite spring of Example 2 is 97%, and the rebound retention rate of the ceramic composite spring of Example 3 is 99%. By comparing the rebound performance of Example 1 with Comparative Examples 1 to Comparative Examples 3, it can be seen that the rebound performance of Example 1 is significantly improved compared to Comparative Examples 1 to Comparative Examples 3.

[0270] (III) Performance stability test

[0271] The present invention tests the performance stability of the ceramic composite springs of Examples 1 to 3 and Comparative Examples 1 to 3, respectively. And the testing method is: the ceramic composite springs of Examples 1 to 3 and Comparative Examples 1 to 3 are aged 100 times, and the conditions of each aging treatment are: first, keep warm in a vacuum furnace at 1350°C for 1 hour, and then cool to room temperature in an air environment. Then, the stiffness and mass of the ceramic composite springs of Examples 1 to 3 and Comparative Examples 1 to 3 after 100 aging treatments are tested, and the degree of change in the stiffness and mass of the springs, that is, the stiffness retention rate and mass loss rate of the springs after aging are used to evaluate the performance stability of the springs, and the obtained results of the stiffness retention rate and mass loss rate after aging are summarized as shown in Table 4.

[0272] Among them, the stiffness retention rate after aging = the stiffness of the spring after aging / the original stiffness of the spring×100%.

[0273] Mass loss rate after aging = 100% - (mass of the spring after aging / original mass of the spring) x 100%.

[0274] Table 4 Stiffness and quality test results of ceramic composite springs after 100 aging treatments

[0275] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Stiffness retention after aging 85% 82% 87% 54% 79% 71% Mass loss rate after aging 0.02% 0.03% 0.01% 1.08% 0.02% 0.45%

[0276] It can be seen from the test results in Table 4 that for the carbon-based composite material spring based on carbon fiber reinforcement of Comparative Example 1, the stiffness retention rate after aging of Examples 1 to 3 is significantly improved, and the mass loss rate after aging is significantly reduced. And by comparing the stiffness retention rate after aging and the mass loss rate after aging of Example 1 with Comparative Examples 1 to 3, it can be seen that the stiffness retention rate after aging of Example 1 is significantly improved, and the mass loss rate after aging is significantly reduced relative to Comparative Examples 1 to 3.

[0277] In summary, the material selection of the fiber material and the interface phase layer, and the form of the ceramic matrix layer, the rare earth co-diffusion layer and the surface reinforcement layer will affect the stiffness of the spring, the resilience of the spring and the performance stability of the spring. This also shows that the improvement of the stiffness of the spring, the resilience of the spring and the performance stability of the spring by the present invention is not achieved by adjusting a single factor, but is achieved by the synergistic effect of various factors.

[0278] Obviously, the above embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A method for preparing a ceramic composite spring, characterized in that: The following steps are involved: Select the corresponding spring mold according to the required spring structure; In an atmosphere containing a silicon carbide source, a silicon carbide ceramic layer is deposited on the surface of the spring mold by a chemical vapor deposition method to obtain a stabilized spring mold; Plying a plurality of strands of silicon carbide fibers together and then weaving them to obtain a fiber braided body; embedding the fiber braided body into the stabilized spring mold and fixing it to obtain a spring braided body; In an atmosphere containing a boron nitride source, a layer of boron nitride is deposited inside and on the surface of the spring braid as an interface phase layer by chemical vapor deposition to obtain a modified spring braid; In an atmosphere containing a silicon carbide source, a ceramic matrix layer is deposited on the surface of the interface phase layer by chemical vapor deposition, and demolding is performed to obtain a spring blank; Using a rare earth mixture containing at least two rare earth oxides as an embedding agent, the spring blank is subjected to embedding infiltration treatment by an embedding infiltration method, so as to form a rare earth co-infiltration layer on the surface of the ceramic matrix layer, thereby obtaining a stabilized spring blank; Dispersing carbide powder in an organic solvent to obtain a coating slurry; applying the coating slurry to the surface of the stabilized spring blank, and after drying, using a chemical vapor deposition method to transform the coating slurry into a surface reinforcement layer to obtain a spring semi-finished product; The semi-finished spring product is polished to remove defects and impurities on the surface of the semi-finished spring product to obtain the ceramic composite material spring.

2. The preparation method according to claim 1, characterized in that The process parameters of the braiding process are: The number of strands of the silicon carbide fiber is 2 to 6; The weaving mode is any one of three-dimensional four-directional, three-dimensional six-directional and two-dimensional circumferential weaving modes; The warp and weft weaving angles are 17° to 38°.

3. The preparation method according to claim 1, characterized in that: When depositing the interface phase layer, the process conditions of chemical vapor deposition are: Under the pressure condition of 100Pa to 3000Pa, the temperature is raised to 680°C to 840°C and kept at this temperature for 4h to 8h; then an atmosphere containing a boron nitride source is introduced and deposited for 24h to 36h; Perform the above steps 1 to 2 times, and then cool to room temperature; The atmosphere containing the boron nitride source is a mixed gas composed of argon, hydrogen, ammonia and boron trichloride; and the flow ratio of the argon, hydrogen, ammonia and boron trichloride is 1:5-8:10-15:10-15.

4. The preparation method according to claim 1, characterized in that: When depositing the ceramic matrix layer, the process conditions of chemical vapor deposition are: Under a pressure of 500Pa to 3000Pa, the temperature is raised to 1000°C to 1200°C and kept at this temperature for 1h to 2h; then a mixed gas consisting of trichloromethylsilane, hydrogen and argon is introduced, and after deposition for 52h to 64h, the introduction of trichloromethylsilane is stopped, the temperature is kept at this temperature for 1h to 2h, and then the temperature is lowered to room temperature; Perform the above steps 4 to 8 times, then demould; Wherein, the flow ratio of trichloromethylsilane, hydrogen and argon is 1:5-15:15-25.

5. The preparation method according to claim 1, characterized in that: The raw materials for preparing the embedding agent used in the embedding infiltration treatment are composed of the following components by mass percentage: SiC 10%~25%, CeO2 1%~5%, Y2O3 4%~6%, La2O3 0.5%~2%, and the balance is Al2O3, totaling 100%.

6. The preparation method according to claim 1, characterized in that: The embedding infiltration treatment is carried out by the following steps: Covering the surface of the workpiece with an embedding agent to a thickness of 0.5 mm to 3 mm to obtain an embedding mixture; The embedding mixture is heated to 1300° C. to 1450° C. at 5 Pa to 150 Pa, kept at this temperature for 0.5 h to 1.5 h, and then cooled to room temperature to obtain the stabilized spring blank.

7. The preparation method according to claim 1, characterized in that: When a silicon carbide ceramic layer is deposited on the surface of the spring mold, the process conditions of chemical vapor deposition are: Under a pressure of 20Pa to 150Pa, the spring mold is heated to 1200°C to 1300°C and kept warm for 4h to 8h; then a mixed gas consisting of trichloromethylsilane, hydrogen and argon is introduced, and after deposition for 4h to 12h, the introduction of trichloromethylsilane is stopped, and the temperature is kept warm for 1h to 2h, and then the temperature is lowered to room temperature; Wherein, the flow ratio of trichloromethylsilane, hydrogen and argon is 1:3-5:10-12.

8. The preparation method according to claim 1, characterized in that: The carbide powder is one or more of silicon carbide powder, silicon carbide whisker and zirconium carbide powder; The organic solvent is one or more of polycarbosilane, xylene and polypropylene alcohol; The usage ratio of the carbide powder to the organic solvent is 1 mg: 5 mL to 25 mL.

9. The preparation method according to claim 1, characterized in that: The coating slurry has a sizing amount of 30 g / m 2 ~50g / m 2 .

10. A ceramic composite material spring prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Forming device and manufacturing method of ceramic spring

    CN103707390A

  • Preparation method for photocured 3D-printed spiral type ceramic spring

    CN109867527A

  • Mold and method for preparing ceramic matrix composite coil spring of SiC fiber

    CN110282981A

  • Mold and method for preparing ceramic matrix composite wave spring

    CN110330355A

  • Rare earth oxide modified silicon carbide ceramic based composite material and preparation method thereof

    CN110407597A